2014
DOI: 10.1080/02701367.2014.930407
|View full text |Cite
|
Sign up to set email alerts
|

White Blood Cell Counts Mediate the Effects of Physical Activity on Prostate-Specific Antigen Levels

Abstract: After adjustments, results showed that moderate-to-vigorous physical activity (MVPA) was inversely associated with WBC count (b = - .03; 95% CI [ - 0.04, - 0.006; p = .01), and WBC count (b = .10; 95% CI [0.009, 0.18; p = .04) was positively associated with PSA. Both the Sobel (coef. = - .004, SE = .002; z = - 2.0; p = .03) and the Aroian (coef. = - .004, SE = .002; z = - 1.9; p = .03) tests demonstrated that WBC mediated the relationship between physical activity and PSA. Additionally, among 107 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Thus, it may reduce the body's inflammation and the risk of inflammation-induced diseases if the number of leukocytes can be kept at an appropriate level. Studies have reported regular exercise, particularly in more moderate-tovigorous physical activity, can have an anti-inflammatory effect and reduce the odds of elevated white blood cell count (51,60,61). Although previous studies focused on elite athletes who practice water sports (62), cyclists who participate in intense endurance exercise (63) have higher levels of inflammation and low immune function.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it may reduce the body's inflammation and the risk of inflammation-induced diseases if the number of leukocytes can be kept at an appropriate level. Studies have reported regular exercise, particularly in more moderate-tovigorous physical activity, can have an anti-inflammatory effect and reduce the odds of elevated white blood cell count (51,60,61). Although previous studies focused on elite athletes who practice water sports (62), cyclists who participate in intense endurance exercise (63) have higher levels of inflammation and low immune function.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariable linear regression analysis, using the median value of each quintile as a continuous variable, was performed to calculate the p for trend. Potential confounding variables were selected through a comprehensive literature review and the preliminary analysis [ 29 , 30 , 31 , 32 ]. Consequently, four models were built as follows: Model 1 was an unadjusted; Model 2 was adjusted for age; Model 3 was adjusted for age, sex, BMI, education level, and physical activity level; and Model 4 included all variables of Model 3 plus alcohol consumption, smoking status, comparison with normal meals, meat and meat products, sweets, and total energy intake.…”
Section: Methodsmentioning
confidence: 99%
“…We observed an inverse association between leisure-time physical activity level and WBC count. Large observational studies consistently reported that individuals performing more frequent or more intense physical activity, regardless of leisure-time or total physical activity, had a lower WBC count (17,20,22,23,28,30,31). A higher objectively measured moderate-to-vigorous physical activity level was associated with a lower WBC count in the US adult population, healthy US male population, and US youth population in previous NHANES studies (17,20,30).…”
Section: Discussionmentioning
confidence: 83%
“…Large observational studies consistently reported that individuals performing more frequent or more intense physical activity, regardless of leisure-time or total physical activity, had a lower WBC count (17,20,22,23,28,30,31). A higher objectively measured moderate-to-vigorous physical activity level was associated with a lower WBC count in the US adult population, healthy US male population, and US youth population in previous NHANES studies (17,20,30). Another NHANES study observed that engaging in physical activity 22 or more times per month was associated with a 41% reduction in risk of a high WBC count (> 9.55×10 9 cells/L), compared to engaging in activity less than four times per month (28).…”
Section: Discussionmentioning
confidence: 99%